Dynamic female labor supply - Zvi Eckstein; Osnat Lifshitz (Institute for the Study of Labor (IZA), 2009)
The increase in female employment and participation rates is one of the most dramatic economic changes to have taken place during the last century. However, while the employment rate of married women more than doubled during the last fifty years, that of unmarried women remained almost constant. In order to empirically analyze these trends we divide the paper into two parts: In the first, we empirically estimate a traditional female dynamic labor supply model using an extended version of Eckstein and Wolpin (1989) in order to compare the various explanations in the literature for the observed trends. The main finding is that the rise in education levels accounts for about one-third of the increase in female employment while about 40 percent remains unexplained by observed household characteristics. We show that this unexplained portion can be empirically attributed to changes in preferences or the costs of childrearing and household maintenance. In the second part, we formulate and estimate a new framework for the couple intra-family game that is then used to analyze the household dynamic labor supply. We find that female labor supply may have increased significantly due to a change in the form of the household game.
Keywords: E24; J2; J3; 330; Dynamic discrete choice; female employment; accounting; household game; Frauenerwerbstätigkeit; Arbeitsangebot; Familienökonomik; Haushaltsökonomik; Spieltheorie; Diskrete Entscheidung; Theorie; USA